Clinical evidence for immunomodulation induced by high-dose melphalan and autologous blood stem cell transplantation as cause for complete clinical remission of multiple myeloma-associated cryoglobulin-vasculitis - Hillengaß, Jens; Ho, Anthony Dick; Goldschmidt, Hartmut; Waldherr, Rüdiger; Möhler, Thomas (International journal of hematology, 2008)
We present a case report of a patient with cryoglobulin-vasculitis caused by multiple myeloma in Durie/Salmon stage I refractory to conventional therapy modalities treated with high-dose chemotherapy followed by autologous blood stem cell transplantation. While clinical symptoms of vasculitis disappeared, elevated cryoglobulin levels persisted. Therefore we conclude that the relief of symptoms was caused by an immunomodulation induced by the autologous stem cell transplantation.
Gesehen am 14.01.2022